Scattering Analysis of a Compact Dipole Array with Series and Parallel Feed Network including Mutual Coupling Effect - H. L. Sneha; Hema Singh; R. M. Jha (International Journal of Antennas and Propagation)
The current focus in defense arena is towards the stealth technology with an emphasis to control the radar cross-section (RCS). The scattering from the antennas mounted over the platform is of prime importance especially for a low-observable aerospace vehicle. This paper presents the analysis of the scattering cross section of a uniformly spaced linear dipole array. Two types of feed networks, that is, series and parallel feed networks, are considered. The total RCS of phased array with either kind of feed network is obtained by following the signal as it enters through the aperture and travels through the feed network. The RCS estimation of array is done including the mutual coupling effect between the dipole elements in three configurations, that is, side-by-side, collinear, and parallel-in-echelon. The results presented can be useful while designing a phased array with optimum performance towards low observability.